La démesure des listes du Conseil des Indes au xviie siècle - Guillaume Gaudin (Mélanges de la Casa de Velázquez, 2014)
From the beginning of the 16th century, the Spanish monarch entrusted the government of the Hispano-American territories to the Consejo de Indias. In the 17th century, intent on achieving better control of the vast and far-flung territories of the western Indies, the monarchy ordered a census and a list of all the civil offices and ecclesiastical benefices granted by Philip IV. For that task, the list was the instrument par excellence used in their daily routine—manejo de papeles—by the bureaucrats in Madrid. From 1630 to 1660, a clerk in the secretariat of New Spain, Juan Díez de la Calle, a relator, Antonio de León Pinelo, and the chronicler of the Indies, Gil González Dávila, worked on several lists which paint a picture of the Spanish leviathan. The extraordinary scale of the lists lends some glory to the Spanish enterprise in America—they afford the reader a notion of the general scale of the American territories and an appreciation of the extent of the royal power and the evangelising ardour of the Crown.